Landscape Motives in the Print Graphic of Hans Burgkmair the Elder (1473–1531) - Mikhailova, Ljudmila V. (Actual Problems of Theory and History of Art, 2013)
The author analyses composition structure and meaning value of landscape fragments of print graphic works of German Renaissance artist Hans Burgkmair the elder. Main trends in the evolution of landscape motives in different periods of the painter’s work are revealed. In the article are also made suppositions about the origin of these motives in the creative work of Hans Burgkmair. Some works by Italian and German artists and the poetry of Conrad Celtis are discussed in this connection.